Assessment of radiological incident at potential nuclear power plant sites in Malaysia using Hybrid Single Particle Langrangian Integrated Trajectory simulation - Jamaludin, Amirul Fakhruddin (2023)
After every nuclear-related incident, the main health threat is the radiation emitted off-site. The 2011 Fukushima Daiichi nuclear power plant incident exemplifies this, as it released radionuclides that posed health risks locally and to neighboring countries. Simulating hypothetical radiological incidents is essential for training, assessing response plans, mitigating risks, and enhancing coordination to ensure effective preparedness and response. This study simulated a scenario similar to the Fukushima incident at three potential nuclear power plant sites in Malaysia using the Hybrid Single Particle Lagrangian Integrated Trajectory (HYSPLIT) model. This model tracks air parcel trajectories and atmospheric dispersion of radioactive emissions. The simulation indicated that radionuclides traveled west and northwest from the Rungkup, Perak (S1) and Jugra, Kuala Langat, Selangor (S2) sites. For the Tenggaroh, Mersing, Johor (S3) site, the dispersion was to the south. Air concentration measurements showed no radionuclide activity between 9 and 12 hours after the incident. Ground deposition results revealed that S1 and S2 covered approximately 1500 km² and 3025 km², respectively. S3 had the largest affected area of around 4537 km² but the lowest maximum dose reading of about 7.9 mSv within 36 hours. Mortality rates at 36 hours were highest at S2 (19.7 deaths per 1000 persons) compared to S1 (5.82 deaths) and S3 (1.31 deaths). Similarly, radiationinduced disease rates were highest at S2 (22.7 cases per 1000 persons) compared to S1 (6.72 cases) and S3 (1.52 cases). The Linear No-Threshold (LNT) model, endorsed by the International Commission on Radiological Protection (ICRP), predicts that even low radiation doses proportionately increase cancer risk. This study generally found that a hypothetical accident would contaminate areas around the three potential nuclear power plant sites in Malaysia, emphasizing the need for effective preparedness and response strategies.